Method for removing iron and copper from molybdenite
Through vacuum smelting and magnesium chloride treatment, the problem of removing iron and copper from molybdenite was solved, efficient, low-cost and environmentally friendly molybdenum recovery was achieved, the process was simplified, and the use of strong acid and molybdenum loss were avoided.
Patent Information
- Application Number
- CN202510955224.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-11
- Publication Date
- 2025-09-23
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallurgical extraction, in particular to a method for removing iron and copper from molybdenite. Background Art
[0002] Molybdenum disulfide (MoS2) has attracted significant attention due to its potential applications in diverse fields, including mechanics and electronics, photocatalysts, sensors, nanocomposites, batteries, superlubricants, and hydrogen storage. Molybdenite, the most important molybdenum mineral resource, is obtained from porphyry molybdenum and copper-molybdenum ores via froth flotation. Chalcopyrite, pyrite, and other minerals may be co-floated with MoS2. Therefore, molybdenite may contain other minerals, including chalcopyrite (CuFeS2), chalcocite (Cu2S), covellite (CuS), pyrite (FeS2), and quartz (SiO2). The presence of Fe and Cu compounds significantly impacts the performance of MoS2. According to GB / T23271-2009, the minimum acceptable Fe content is no more than 0.7wt%. However, for use in high-end industries, MoS2 requires even higher Fe contents. Increased Fe and Cu content significantly impacts its application in these industries.
[0003] However, the current technology for removing Fe and Cu from molybdenite mainly uses a wet impurity removal process based on acid leaching. The waste liquid of this process is highly toxic, the treatment cost is expensive, and there is a serious loss of molybdenum. The previously proposed vacuum chlorination method for removing iron and copper requires water leaching followed by recrystallization for the recovery of the chlorinating agent, which is a relatively cumbersome process. Summary of the Invention
[0004] The present invention provides a method for removing iron and copper from molybdenite, aiming to solve the problems of long process, high toxicity of process waste liquid, high treatment cost and serious molybdenum loss in the current technology for removing iron and copper from molybdenite. Compared with the existing vacuum chlorination process, the method of the present invention has a shorter process and avoids the problem of molybdenum disulfide being consumed by chlorination due to excessively high temperature, and can directly recover the chlorinating agent in one step for repeated use.
[0005] The technical solutions of the present invention are as follows: A method for removing iron and copper from molybdenite comprises the following steps: Molybdenite powder and magnesium chloride powder are added to the containing cavity of a graphite crucible and mixed to obtain a smelting raw material. The smelting raw material is melted in a vacuum atmosphere and then cooled to obtain a residue and a condensate. The condensate is directly recovered from the condensate tray, and the residue is sequentially soaked in water and acid, and then washed and dried to obtain a residue rich in molybdenum disulfide.
[0006] The mass ratio of the molybdenite powder to the magnesium chloride powder is 1:(0.25~2).
[0007] Calculated by mass fraction, the molybdenite powder comprises: 45-55wt% Mo, 35-38wt% S, 0.5-6wt% Fe, 0.2-6wt% Cu, 0.2-1.5wt% Pb, and the rest are unavoidable impurities.
[0008] The smelting temperature is 800-1100° C., the smelting time is 20-80 min, and the smelting heating rate is 1° C. / min-10° C. / min.
[0009] The solid-liquid ratio g:mL of the water immersion is 1:(1-5), the water immersion temperature is 25°C-90°C, and the water immersion time is 1-5 hours.
[0010] The solid-liquid ratio g:mL of the acid leaching is 1:(1-5), the acid leaching temperature is 25°C-90°C, and the acid leaching time is 1-5 hours.
[0011] The acid used in the acid leaching is hydrochloric acid, and the mass concentration of the hydrochloric acid is 5% to 15%.
[0012] Beneficial effects of the present invention: The present invention significantly reduces the waste liquid content and treatment cost through vacuum melting and the combination of magnesium chloride additives, effectively shortens the entire process, recovers magnesium chloride in one step, and greatly improves the recovery rate of molybdenum.
[0013] The present invention combines magnesium chloride with vacuum melting to convert impurities into easily volatile chlorides for removal at high temperature, rather than directly dissolving MoS2. Compared with the wet process using strong acid, this method can significantly reduce the wastewater generated by using strong inorganic acid in the impurity removal process of molybdenum disulfide, while greatly shortening the process and improving the total recovery rate and product yield of molybdenum.
[0014] The present invention can efficiently remove sulfides and oxides of iron, copper and other metals in molybdenite, and ultimately obtain a product rich in molybdenum disulfide, thereby achieving green, environmentally friendly, high-recovery, low-cost and short-process iron and copper removal, solving the key defects of the existing wet process and shortening the vacuum chlorination process. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is the XRD pattern of the residue rich in molybdenum disulfide; Figure 2 This is a physical picture of the residue rich in molybdenum disulfide; Figure 3 This is a physical picture of the condensate in the smelting condensate tray; Figure 4 It is the XRD spectrum of the smelting condensate. DETAILED DESCRIPTION
[0016] To make the technical solutions and advantages of the present invention more apparent, the present invention and its beneficial effects will be further described in detail below in conjunction with specific embodiments. The accompanying drawings and the following description are provided to enable those skilled in the art to fully understand the present invention and are not intended to limit the subject matter described in the claims. Unless otherwise specified, all embodiments and alternative embodiments of the present invention can be combined to form new technical solutions.
[0017] The molybdenite used in the present invention is the most important molybdenum ore resource, in which the various elements exist in the form or phase of MoS2, SiO2, CaO, Fe2O3, FeS, FeS2, Al2O3, MgO, K2O, CuO, CuS, etc., among which the presence of Fe and Cu has a serious impact on MoS2. According to GB / T23271-2009, the minimum acceptable Fe content does not exceed 0.7wt%. When used in high-end industries, the Fe content in MoS2 is required to be higher.
[0018] The magnesium chloride (MgCl2) of the present invention reacts with metal oxides and sulfides such as FeS2, FeS, PbS, K2S, K2O, CaO, CuO, etc. in molybdenite at high temperature to form chlorides with lower boiling points, which are removed by volatilization.
[0019] Example 1 S1: Molybdenite powder and magnesium chloride powder are mixed and pressed into sheets to obtain a smelting raw material, which is then placed in a holding cavity of a graphite crucible; wherein the mass ratio of molybdenite powder (Fe: 0.56 wt%, Cu: 0.27 wt%) to magnesium chloride powder is 1:1.5; S2: Cover the graphite cover and place the smelting raw materials into a high-temperature vacuum furnace. Evacuate to 5Pa~10Pa. In a vacuum atmosphere, heat to 750℃ at a heating rate of ≈5℃ / min and melt for 60min. After high-temperature melting, cool to obtain a residue in a graphite crucible and a condensate on a condensation tray. S3: Take the residue and directly add water to the residue at a solid-liquid ratio of 1:2 g:mL, soak it in water at 25°C for 1 hour to remove a small amount of non-volatile chloride, then wash and dry, add 5% hydrochloric acid at a solid-liquid ratio of 1:2 g:mL after drying, and acid-leach it at 50°C for 3 hours to remove the introduced magnesium compounds by acid leaching. After acid leaching, wash and dry to obtain a residue rich in molybdenum disulfide; The chlorinating agent was collected from the condensate tray. The recovery rate of the chlorinating agent was approximately 43.49%. This may be because the smelting temperature was low, resulting in a low recovery rate of magnesium chloride. The collected chlorinating agent was returned to step S1 and mixed with molybdenite to conduct the chlorination experiment again.
[0020] Example 2 S1: Molybdenite powder and magnesium chloride powder are mixed and pressed into sheets to obtain a smelting raw material, which is then placed in a holding cavity of a graphite crucible; wherein the mass ratio of molybdenite powder (Fe: 0.56 wt%, Cu: 0.27 wt%) to magnesium chloride powder is 1:1.5; S2: Cover the graphite cover and place the smelting raw materials into a high-temperature vacuum furnace. Evacuate to 5Pa~10Pa. In a vacuum atmosphere, heat to 1050℃ at a heating rate of ≈5℃ / min and melt for 60min. After high-temperature melting, cool to obtain a residue in a graphite crucible and a condensate on a condensation tray. S3: Take the residue and directly add water to the residue at a solid-liquid ratio of 1:2 g:mL, soak it in water at 25°C for 2 hours to remove a small amount of non-volatile chloride, then wash and dry it, add 5% hydrochloric acid at a solid-liquid ratio of 1:2 g:mL after drying, and acid-leach it at 90°C for 1 hour to remove the introduced magnesium compounds by acid leaching. After acid leaching, wash and dry it to obtain a residue rich in molybdenum disulfide; The condensate tray is taken out and the chlorinating agent is collected from the condensate tray. The recovery rate of the chlorinating agent is ≥95%. The collected chlorinating agent is returned to step S1 and mixed with molybdenite to perform the chlorination experiment again.
[0021] Example 3 S1: Molybdenite powder and magnesium chloride powder are mixed and pressed into sheets to obtain a smelting raw material, which is then placed in a holding cavity of a graphite crucible; wherein the mass ratio of the molybdenite powder (Fe: 0.56 wt%, Cu: 0.27 wt%) to the magnesium chloride powder is 1:1; S2: Cover the graphite cover and place the smelting raw materials into a high-temperature vacuum furnace. Evacuate to 5Pa~10Pa. In a vacuum atmosphere, heat to 800℃ at a heating rate of ≈5℃ / min and melt for 80min. After high-temperature melting, cool to obtain a residue in a graphite crucible and a condensate on a condensation tray. S3: Take the residue and directly add water to the residue at a solid-liquid ratio of 1:2 g:mL, soak it in water at 50°C for 2 hours to remove a small amount of non-volatile chloride, then wash and dry it, add 5% hydrochloric acid at a solid-liquid ratio of 1:2 g:mL after drying, and acid-leach it at 40°C for 5 hours to remove the introduced magnesium compounds by acid leaching. After acid leaching, wash and dry it to obtain a residue rich in molybdenum disulfide; The condensate tray is taken out and the chlorinating agent is collected from the condensate tray. The recovery rate of the chlorinating agent is ≥95%. The collected chlorinating agent is returned to step S1 and mixed with molybdenite to perform the chlorination experiment again.
[0022] Example 4 S1: Molybdenite powder and magnesium chloride powder are mixed and pressed into sheets to obtain a smelting raw material, which is then placed in a holding cavity of a graphite crucible; wherein the mass ratio of molybdenite powder (Fe: 0.56wt%, Cu: 0.27wt%) to magnesium chloride powder is 1:2; S2: Cover the graphite cover and place the smelting raw materials into a high-temperature vacuum furnace. Evacuate to 5Pa~10Pa. In a vacuum atmosphere, heat to 950℃ at a heating rate of ≈5℃ / min and melt for 60min. After high-temperature melting, cool to obtain a residue in a graphite crucible and a condensate on a condensation tray. S3: Take the residue and directly add water to the residue at a solid-liquid ratio of 1:2 g:mL, soak it in water at 25°C for 4 hours to remove a small amount of non-volatile chloride, then wash and dry it, add 5% hydrochloric acid at a solid-liquid ratio of 1:2 g:mL after drying, and acid-leach it at 60°C for 1 hour to remove the introduced magnesium compounds by acid leaching. After acid leaching, wash and dry it to obtain a residue rich in molybdenum disulfide; The condensate tray is taken out and the chlorinating agent is collected from the condensate tray. The recovery rate of the chlorinating agent is ≥95%. The collected chlorinating agent is returned to step S1 and mixed with molybdenite to perform the chlorination experiment again.
[0023] Example 5 S1: Molybdenite powder and magnesium chloride powder are mixed and pressed into sheets to obtain a smelting raw material, which is then placed in a holding cavity of a graphite crucible; wherein the mass ratio of molybdenite powder (Fe: 0.56wt%, Cu: 0.27wt%) to magnesium chloride powder is 1:2; S2: Cover the graphite cover and place the smelting raw materials into a high-temperature vacuum furnace. Evacuate to 5Pa~10Pa. In a vacuum atmosphere, heat to 1100℃ at a heating rate of ≈1℃ / min and melt for 20min. After high-temperature melting, cool to obtain a residue in a graphite crucible and a condensate on a condensation tray. S3: Take the residue and directly add water to the residue at a solid-liquid ratio of 1:1 g:mL, and soak it in water at 25°C for 5 hours to remove a small amount of non-volatile chloride, then wash and dry, and add 15% hydrochloric acid at a solid-liquid ratio of 1:1 g:mL after drying, and acid-leach it at 25°C for 3 hours to remove the introduced magnesium compounds by acid leaching. After acid leaching, wash and dry to obtain a residue rich in molybdenum disulfide; The condensate tray is taken out and the chlorinating agent is collected from the condensate tray. The recovery rate of the chlorinating agent is ≥85%. The collected chlorinating agent is returned to step S1 and mixed with molybdenite to perform the chlorination experiment again.
[0024] Example 6 S1: Molybdenite powder and magnesium chloride powder are mixed and pressed into sheets to obtain a smelting raw material, which is then placed in a holding cavity of a graphite crucible; wherein the mass ratio of molybdenite powder (Fe: 0.56 wt%, Cu: 0.27 wt%) to magnesium chloride powder is 1:0.25; S2: Cover the graphite cover and place the smelting raw materials into a high-temperature vacuum furnace. Evacuate to 5Pa~10Pa. In a vacuum atmosphere, heat to 1000℃ at a heating rate of ≈10℃ / min and melt for 30min. After high-temperature melting, cool to obtain a residue in a graphite crucible and a condensate on a condensation tray. S3: Take the residue and directly add water to the residue at a solid-liquid ratio of 1:5 g:mL, soak it in water at 90°C for 1 hour to remove a small amount of non-volatile chloride, then wash and dry, add 10% hydrochloric acid at a solid-liquid ratio of 1:5 g:mL after drying, and acid-leach it at 90°C for 1 hour to remove the introduced magnesium compounds by acid leaching. After acid leaching, wash and dry to obtain a residue rich in molybdenum disulfide; Take the condensate tray and collect the chlorinating agent from the condensate tray. The recovery rate of the chlorinating agent is ≥90%. The collected chlorinating agent is returned to S1 and mixed with molybdenite to conduct the chlorination experiment again.
[0025] Example 7 S1: Molybdenite powder and calcium chloride powder are mixed and pressed into sheets to obtain a smelting raw material, which is then placed in a holding cavity of a graphite crucible; wherein the mass ratio of molybdenite powder (Fe: 0.56wt%, Cu: 0.27wt%) to calcium chloride powder is 1:2; S2: Cover the graphite cover and place the smelting raw materials into a high-temperature vacuum furnace. Evacuate to 5Pa~10Pa. In a vacuum atmosphere, heat to 950℃ at a heating rate of ≈5℃ / min and melt for 60min. After high-temperature melting, cool to obtain a residue in the graphite crucible and a condensate on the condensation tray. The condensate is the chlorinated impurity volatiles. S3: Take the residue and directly add water to the residue at a solid-liquid ratio of 1:2 g:mL, soak it in water at 25°C for 4 hours, then wash and dry it. After drying, add 5% hydrochloric acid at a solid-liquid ratio of 1:2 g:mL, acid-leach it at 60°C for 1 hour, wash and dry it to obtain the product; The water-immersion solution is taken for evaporation and crystallization, and calcium chloride is finally obtained, and then returned to S1 for the experiment.
[0026] Take the molybdenite powder separately, evacuate to 5Pa~10Pa, and heat to 950℃ and melt for 60min under the condition of heating rate ≈10℃ / min in vacuum atmosphere. Cool down after high temperature melting, and no volatiles of Fe and Cu are obtained in the condensation plate. Add water at a solid-liquid ratio of g:mL of 1:2, soak in water at 25℃ for 4h, then wash and dry. Add hydrochloric acid with a mass concentration of 5% at a solid-liquid ratio of g:mL of 1:2 to the residue after drying, and acid soak at 60℃ for 1h. Wash and dry to obtain the product, and the composition of the product is not much different from that of the original molybdenite powder.
[0027] The MoS2-rich residue and condensate in Example 2 were characterized by XRD, and the Fe and Cu residual rates of the residues after water immersion in all examples were measured. The method included the following steps: pressing the residue after water immersion into a pellet, selecting the target material Cu Kα, λ=1.5406 Å, setting the scanning range to 5°~95°, the step size to 0.02° and the scanning speed to 5° / min~10° / min, and recording the diffraction pattern through the detector.
[0028] Figure 1 This is the XRD spectrum of the residue rich in molybdenum disulfide in Example 2. It was found through XRD that no Fe and Cu impurities were found in the residue. Figure 2 This is a physical picture of the molybdenum disulfide-rich residue of Example 2; Figure 3 This is a physical picture of the condensate in the condensation tray after vacuum chlorination in Example 2. The chlorinating agent can be directly recovered by scraping; Figure 4 This is the XRD spectrum of the condensate in the condensation tray after vacuum chlorination in Example 2. Through XRD testing of the condensate, it was found that the condensate is mainly composed of MgCl2, so it can be directly returned to step S1 to be used as a chlorinating agent.
[0029] The residual amounts of Fe and Cu and the direct yield of MgCl2 were tested on the MoS2-rich residues after water immersion in Examples 1 to 4, and the residual amounts of Fe and Cu were tested on the MoS2-rich residue after water immersion in Example 7. The results were measured by ICP-OES. See Table 1. As can be seen from Table 1, this method has a significant effect on the removal of Fe and Cu. At the same time, the chlorinating agent can be easily recovered and directly reused after being scraped from the condensate tray. Compared with the conventional wet method, this method does not produce a large amount of strong inorganic acid waste liquid, shortens the vacuum chlorination step, is simple to operate, and is safe. It also has very obvious advantages over Example 7.
[0030] Table 1
[0031] In summary, the present invention successfully avoids the use of strong inorganic mixed acid through vacuum smelting and magnesium chloride additive, significantly reduces the toxicity of waste liquid and treatment cost, effectively reduces the loss of molybdenum disulfide in the impurity removal process, and greatly improves the recovery rate of molybdenum; at the same time, the method can efficiently remove Fe, Cu compounds and other metal oxides in molybdenite, and ultimately obtain a product rich in molybdenum disulfide, achieving green, environmentally friendly, high recovery, and low-cost removal of Fe and Cu, solving the key defects of the existing wet process and shortening the existing vacuum chlorination process.
[0032] The above description is only a partial or preferred embodiment of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural transformations made by using the contents of the present invention description and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.
Claims
1. A method for removing iron and copper from molybdenite, characterized in that: The following steps are involved: Mixing molybdenite powder and magnesium chloride powder to obtain smelting raw materials; The smelting raw materials are vacuum melted and then cooled to obtain residues and condensates; The condensate is directly recycled; The residue is sequentially subjected to water leaching and acid leaching, and then washed and dried to obtain a residue rich in molybdenum disulfide.
2. The method for removing iron and copper from molybdenite according to claim 1, wherein: The mass ratio of the molybdenite powder to the magnesium chloride powder is 1:(0.25~2).
3. The method for removing iron and copper from molybdenite according to claim 1, wherein: Calculated by mass fraction, the molybdenite powder comprises: 45-55wt% Mo, 35-38wt% S, 0.5-6wt% Fe, 0.2-6wt% Cu, 0.2-1.5wt% Pb, and the rest are unavoidable impurities.
4. The method for removing iron and copper from molybdenite according to claim 1, wherein: The smelting temperature is 800-1100° C., the smelting time is 20-80 min, and the heating rate is 1° C. / min-10° C. / min.
5. The method for removing iron and copper from molybdenite according to claim 1, wherein: The solid-liquid ratio g:mL of the water immersion is 1:(1-5), the water immersion temperature is 25°C-90°C, and the water immersion time is 1h-5h.
6. The method for removing iron and copper from molybdenite according to claim 1, wherein: The solid-liquid ratio g:mL of the acid leaching is 1:(1-5), the acid leaching temperature is 25°C-90°C, and the acid leaching time is 1h-5h.
7. The method for removing iron and copper from molybdenite according to claim 1, wherein: The acid used in the acid leaching is hydrochloric acid, and the mass concentration of the hydrochloric acid is 5% to 15%.